International Financial Reporting Standards (IFRS) and Reporting Quality in Nigeria: An Assessment of Selected Quoted Firms - Aminu Abdullahi; Musa Yelwa Abubakar (International Business and Accounting Research Journal, 2020)
This study investigates the effect of IFRS adoption on reporting quality in Nigeria. Secondary data were sourced from financial reports of a sample of 79 quoted Nigerian firms, with the help of Nimegen Centre for Economics (NiCE) qualitative reporting index for reporting quality. The study covered a period of 10 years, i.e. 2007 to 2011 as SAS regime and 2012 to 2016 IFRS regime. ANOVA test and descriptive analysis, were utilised for the analysis. The study concludes that, IFRS adoption has made significant positive difference in the extent of reporting quality. It is recommended that Nigerian firms should adopt appropriate measures to improve the level of relevance, comparability and verifiability of their financial reports through provision of more forward looking information, reduction in the use of technical jargons and appointment of more reputable audit firms.